THE INFLUENCE OF ASSET TANGIBILITY, GROWTH OPPORTUNITY, AND BUSINESS RISK ON CAPITAL STRUCTURE IN THE PROPERTY AND REAL ESTATE SECTOR OF THE INDONESIA STOCK EXCHANGE - Wulandari Cahyani Putri (International Journal Multidisciplinary Science, 2025)
This study examines the influence of asset tangibility, growth opportunity, and business risk on capital structure in property and real estate companies listed on the Indonesia Stock Exchange (IDX) from 2016 to 2018. Using a quantitative associative approach, the research analyzes secondary data from financial reports of 22 companies. The results indicate that asset tangibility has a negative impact on capital structure, suggesting that companies with higher tangible assets rely more on internal financing. Growth opportunity positively affects capital structure, meaning companies with strong growth potential tend to use more debt for expansion. Business risk also positively impacts capital structure, implying that higher business risks encourage greater debt usage for financial discipline. These findings align with agency theory and signal theory, highlighting the importance of internal factors in financing decisions. This research provides insights for managers and investors in optimizing capital structure strategies.